Effects of Perioperative Epidural Analgesia on Cancer Recurrence and Survival - Zhang, Donghang; Jiang, Jingyao; Liu, Jin; Zhu, Tao; Huang, Han; Zhou, Cheng (Frontiers in Oncology, 2022)
Surgical resection is the main curative avenue for various cancers. Unfortunately, cancer recurrence following surgery is commonly seen, and typically results in refractory disease and death. Currently, there is no consensus whether perioperative epidural analgesia (EA), including intraoperative and postoperative epidural analgesia, is beneficial or harmful on cancer recurrence and survival. Although controversial, mounting evidence from both clinical and animal studies have reported perioperative EA can improve cancer recurrence and survival via many aspects, including modulating the immune/inflammation response and reducing the use of anesthetic agents like inhalation anesthetics and opioids, which are independent risk factors for cancer recurrence. However, these results depend on the cancer types, cancer staging, patients age, opioids use, and the duration of follow-up. This review will summarize the effects of perioperative EA on the oncological outcomes of patients after cancer surgery.